Corticospinal Dysgenesis and Congenital Hemiplegia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
A diffusion tensor imaging technique was compared with conventional MRI to measure and quantify corticospinal dysgenesis in 12 patients with congenital hemiplegia and 12 matched control subjects, in a study at Universite Catholique de Louvain, Brussels, Belgium.